Simulation and Management of Environmental Disturbances in Flight Simulator X - João Fernando de Sousa Almeida (2017)
The frequency of natural and man-made climatic disasters has been rising in recent years. In order to comprehend, examine, and even combat these occurrences, various vehicles are utilized on missions: aircraft, ships and automobiles represent the majority. Such vehicles may be manned, remote-controlled, or even fully autonomous; the latter being increasingly common.As to provide a way of simulating cooperative multi-vehicle missions, a platform was developed using Microsoft's Flight Simulator X (FSX) as its core and simulation engine. Despite being centered on a flight simulator, it supports vehicles beyond aircraft.Is it possible to create an environmental disturbances manager, and effectively integrate it within the existing platform? Is it feasible to introduce a generic interface for external disaster simulators into the system?A positive answer for these research questions can be an excellent sign that the Platform was effectively improved, and that it became more suitable for a real world application. A neutral or even negative answer may be undesired, however it may still provide a good insight on what is achievable on a similar architecture, and provide the researcher with the knowledge to apply on improving current or future solutions to similar problems.The Platform includes a control panel, which allows for the specification of each mission; an agent to manage traffic; a vehicle control agent; performance analysis; and the basis for a disturbances management tool. The Platform enables the specification and deployment of a wide variety of missions using multiple vehicle types on various simulations. While still technically in prototype stage, the Platform is currently at a fairly advanced level.The Disturbances Manager is responsible for the simulation of environmental anomalies - which may require the intervention of vehicle teams, or have an impact on unrelated vehicular missions; it communicates with the Platform's Control Panel, FSX, and with the Vehicle Control Agents - as to relay the corresponding sensor readings.The Disturbances Manager, at it's current state, allows for the basic specification of disturbances using a graphical interface; these are stored as XML files for future use; this specification is to be further developed, as to encompass the details of all the disturbances to be considered.Given that the Disturbances Manager is to be fully integrated into a distributed simulation platform, similar architectures are being studied and taken into consideration on how to perform said integration.A fire may be spreading on a mountain range, which needs to be located; a hurricane may occur in the set course for an upcoming flight. The Disturbances Manager aims to facilitate the simulation of such events, among others: some may be simulated directly through FSX, others may surpass the limitations of the Flight Simulator and require implementation through the Platform itself - in which case, the Disturbances Manager communicates with the Vehicle Control Agents as to provide the vehicles in the affected area with the sensor readings corresponding to the disturbance at hand (e.g. an automobile being driven in the vicinity of a burning building will get higher temperature and carbon dioxide readings).The main objective for this dissertation is to develop the disturbances management component of the mentioned platform with the objective of simulating a wide array of disturbances, such as fires, pollution, storms, volcanic eruptions and chemical spills. The simulation of such disturbances will allow the posterior automatic adapting of vehicular missions according to the placement, evolution, and sensor readings related to the disturbances at hand (e.g. to avoid a low-visibility area in a commercial flight or to locate the center of a forest fire, in the case of aerial firefighting).